1989
DOI: 10.3171/jns.1989.71.2.0180
|View full text |Cite
|
Sign up to set email alerts
|

Cranial burr hole for revascularization in moyamoya disease

Abstract: Currently, superficial temporal artery-middle cerebral artery (MCA) anastomosis, encephalomyosynangiosis (EMS), and encephalo-duro-arterio-synangiosis are used to treat moyamoya disease and are reported to effectively improve ischemic symptoms. All are methods of reversing the flow of blood from the external carotid artery system into the cortical branches of the MCA. As moyamoya disease advances, these operations alone will predictably not correct the deterioration in blood flow in the territory of the anteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(58 citation statements)
references
References 14 publications
0
56
0
2
Order By: Relevance
“…The multiple cranial bur hole technique is an additional indirect technique that can be used to treat moyamoya disease. 11,84 Until recently, this technique has been used in combination with other techniques, such as the STA-MCA bypass, EMS, EDAS, or pial synangiosis, to provide supplemental collateralization, especially to the frontal and occipital lobes, which typically are not well vascularized by these other techniques. 95 Unfortunately, the rate of collateral development as determined by postoperative angiography is variable.…”
Section: Options For Surgical Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The multiple cranial bur hole technique is an additional indirect technique that can be used to treat moyamoya disease. 11,84 Until recently, this technique has been used in combination with other techniques, such as the STA-MCA bypass, EMS, EDAS, or pial synangiosis, to provide supplemental collateralization, especially to the frontal and occipital lobes, which typically are not well vascularized by these other techniques. 95 Unfortunately, the rate of collateral development as determined by postoperative angiography is variable.…”
Section: Options For Surgical Treatmentmentioning
confidence: 99%
“…12,16,17,29,34,48,54,81,91,113 Revascularization procedures can be divided into 3 main groups: indirect (nonanastomotic) bypass techniques, direct (anastomotic) bypass techniques, and indirect and/or direct bypass techniques combined. Indirect bypass techniques include pial synangiosis, 2,91 EDAS, 67,69 EMS (temporalis muscle with its rich blood supply is sutured to the dura mater), 33 encephaloduroateriomyosynangiosis (EDAMS), 43 ribbon EDAMS, 44 encephalogaleosynangiosis (EGS), 110 encephalogaleomyosynangiosis (EGMS), 92 omental transplantation, 23,31,35 bifrontal encephalogaleoperiosteal synangiosis (EGPS), 42,80 and multiple bur hole surgery, with opening of dura and arachnoid over affected areas, 11,84 as well as a combination of ≥ 1 of these techniques. One of the biggest criticisms of the indirect techniques has been that the beneficial effects are not immediate because it takes ≥ 3-4 months for collaterals to develop, 25,113 and during that time there is a risk of perioperative ischemic stroke.…”
Section: Options For Surgical Treatmentmentioning
confidence: 99%
“…Direct STA-ACA bypass surgery was performed as a secondary surgery for refractory ischemic episodes. 5,7) Indirect bypass surgery targeting the frontal lobe, 21) ribbon EDAMS, 13) burr holes, 1,11) and dural pedicle insertion over the brain surface combined with encephalo-galeo-synangiosis 23) have also been reported. The present study describes the technical procedure to establish vasoreconstructive surgery including direct bypass for the ACA territory at the first intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Various methods of vasoreconstructive surgery are accepted as treatment for moyamoya disease, including direct bypass such as superficial temporal artery (STA) to middle cerebral artery (MCA) bypass 8) ; indirect bypass such as encephalo-duroarterio-synangiosis, 20) encephalo-duro-arterio-myosynangiosis (EDAMS), 12) and omentum transplantation 9) ; multiple burr holes 1,11) ; and a combination of direct and indirect bypasses. 4,10,12) Such methods provide good neovascularization through the extracranial arteries and reduced risk of cerebral ischemia after the surgery.…”
Section: Introductionmentioning
confidence: 99%
“…EMS and EDAS are the two principal procedures for single indirect bypass and have spurred the development of a multitude of variants that have used the scalp arteries, galea, dura mater, muscles, and omentum as donor tissues. 15,17,21,40,59) Endo et al, 2) Kawaguchi et al, 19) and Seinte-Rose et al 52) even reported a multiple burr hole surgery technique for children with moyamoya disease.…”
mentioning
confidence: 99%